2009
DOI: 10.1002/lary.20305
|View full text |Cite
|
Sign up to set email alerts
|

Complications and satisfaction with pediatric osseointegrated external ear prostheses

Abstract: Titanium osseointegrated ear prosthesis is a safe and useful procedure for children with microtia. It should be presented as an option for these patients, with low complication rates and high acceptance rates by the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 9 publications
(8 reference statements)
1
23
1
Order By: Relevance
“…In our study, all patients had a skin reaction at least once, the incidence of which was higher in our study compared to others: Westin et al [9] showed a 3% incidence of significant skin reactions, Hamming et al [3] reported that 3/9 ears developed skin complications. As we found a correlation between residence and the likelihood of skin reactions, we speculate that the increased complications are a result of poor hygiene conditions in China, especially in rural areas.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…In our study, all patients had a skin reaction at least once, the incidence of which was higher in our study compared to others: Westin et al [9] showed a 3% incidence of significant skin reactions, Hamming et al [3] reported that 3/9 ears developed skin complications. As we found a correlation between residence and the likelihood of skin reactions, we speculate that the increased complications are a result of poor hygiene conditions in China, especially in rural areas.…”
Section: Discussioncontrasting
confidence: 41%
“…Westin et al [9] retrospectively analyzed 99 patients with auricular prostheses caused by congenital malformation (58), tumor resection (30), trauma (8) and burns (3), who received 107 prosthetic ears (8 patients had bilateral defects), retained 309 implants (95%) and wear their prosthesis every day, in most cases more than 10 h/day, with a 3% incidence of significant skin reactions. Hamming et al [3] operated 8 patients for congenital microtia; 6/8 had oculoauriculovertebral syndrome, and 2 had isolated microtia. All titanium screws achieved complete osseointegration, and no implants have failed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large portion of literature on osseointegrated auricular reconstruction is based on congenital cases. 5,7,8,12 An area of contention is the use of osseointegrated implants in the pediatric age group, particularly in microtia cases. It has been our practice to dissuade patients from this approach in the primary microtia cases.…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition, there can occasionally be failure of the implant to osseointegrate into the bone. While multiple case reports and limited case series [7][8][9][10][11][12] have been published on osseointegration for auricular reconstruction, there have been few large series looking at overall long-term results and complications. One of the largest series (n ϭ 108) was published in 1999 and showed long-term success when looking at failure of fixtures over time and low complication rates as defined by local skin reaction.…”
mentioning
confidence: 99%